An Investigation Into Cohesive Devices In English Business Articles - Mai Thị Tình (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The study is an attempt to investigate cohesive devices used in English business articles and their distinctive features in terms of meaning. In the study, 400 English business articles in three newspapers: the Wall Street journal, the New York Times and the Economist were selected and collected for investigation. Based on the theoretical background presented in Chapter 2, cohesive devices are explored and analyzed. The theory of cohesion in general and cohesive devices in particular is based on theory of Halliday and Hasan in Cohesion in English (1976). The cohesive devices used in 400 Engish business articles include grammatical cohesive devices (reference, substitution, ellipsis, conjunction) and lexical cohesive devices (repetition, synonymy, hyponymy and collocation). Qualitative and quantitative analysis is done to show the characteristics and frequencies of cohesive devices used in those articles. The findings of the study show the frequency of grammatical and lexical cohesive devices in English business articles in terms of the occurrence and their distinctive features in terms of meaning, which lay the foundations of implications for teaching and learning cohesive devices in English as a foreign language.